Upaya Meningkatkan Hasil Belajar Mata Pelajaran Pendidikan Kewarganegaraan Materi Pancasila dengan Metode Make a match - Herawati, Dina (CV. Publikasi Indonesia, 2022)
The importance of choosing the right learning method in accordance with the material taught by the teacher will determine the success of the teaching and learning process in the classroom. There are several learning methods that can be used by teachers in the teaching and learning process. The make a match learning method is one method that can be used in the teaching and learning process. This learning method was developed by Lorna Curran to overcome various limitations in the teaching and learning process and can also be used to improve student learning outcomes. The purpose of this research is to find out the effectiveness of efforts in realizing fun learning and can improve student learning outcomes. The teacher explains the rules for playing make a match using learning card media, the teacher starts calling students randomly, the teacher instructs students to choose a make a match game card randomly, then the students read the cards he chose, then students look for card pairs. SMA Negeri 2 Pekalongan in Pancasila material in Citizenship Education lessons can increase. Learning with the Make a match learning model is very effectively used to improve student learning outcomes.